ANALISIS KANDUNGAN BIOMASSA DAN KARBON TERSIMPAN (Carbon Stock) PADA PSP (Plot Sampling Parmanent) HUTAN NEGERI SOYA KOTA AMBON. - Yulianus D Komul; Gun Mardiatmoko; Rohny S. Maail (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Carbon stocks while amount of carbon stored on vegetation, other biomass and soil. Effort to reduce greenhouse gas concentrations at atmosphere (emissions) ito reduce CO2 into air. Amount of CO2 on air must be controlled by increasing of CO2 by plants as much as possible and reducing release of emissions as low as possible. Carbon stored reserves should be measured as attempt to carbon stocks in forest to decrease carbon emissions and adverse effects. Research do in September 2015 at parmanent sampling plot on 2012 at Soya included Mount Sirimau . Method of biomass and carbon stocks on Measurement and Calculation of Carbon Stock overall primary forests and secondary forests consist of 409. Total biomass content for For strata of primary forest biomass is 510 with 3590 tons / ha - 786.6950 tons / ha with average content of biomass at 640.4733 tons/ ha. .At secondary forest is 210.1608 tons / ha to 436.6976 tons / ha with 289.4509 tons / ha. Carbon-stored at primary forest is 239.9190 tons / ha to 369.0228 tons / ha with 301.1112 tons / ha. On secondary forest amount of carbon stored is 88.9805 tons / ha to 139.7868 tons / ha and 110.1785 tons / ha.